Teacher perspectives of online continuing professional development in physical education. Issue 4 (4th May 2022) - Lander, Natalie; Lewis, Steven; Nahavandi, Darius; Amsbury, Kyler; Barnett, Lisa M.
ABSTRACT: Continuing professional development (CPD) is important to ensure teachers continuously maintain and update the best practice knowledge and skills needed for the profession. Limited research into CPD in physical education (PE-CPD) suggests that current provisions are largely ineffective, particularly regarding access, and the specific teaching of motor skills (e.g. throw, catch, run). Improved PE-CPD is clearly needed, and online programmes may provide a promising avenue for more accessible and effective delivery. Digital models of PE-CPD are in the early stages of use, and as yet we know very little about PE teachers' experiences of online CPD. Thus, the present study aimed to (i) explore elementary school PE teachers' perceptions of online PE-CPD; and (ii) provide recommendations on the development and provision of future online PE-CPD, with a particular focus on motor skill instruction and assessment. Twenty-two PE teachers participated in focus group discussions, which were analysed in NVivo 11 using an inductive thematic approach. Three major themes and several subthemes were developed from the data. First, there was significant teacher motivation and perceived need for online PE-CPD, mainly in relation to accessibility. Second, and despite this perceived need, teachers reported considerable caution around its use, especially regarding a perceived lack of a 'community of practice'. Third, teachers provided multiple suggestions for future online PE-CPD design and delivery, including that it: (i) be evidence-based; (ii) provide pedagogical content knowledge and not just content knowledge; (iii) be informed by teachers and translatable to practice; (iv) facilitate communities of practice; (v) be interactive; (vi) be simple to navigate; and (vii) be highly visual. It is clear from teacher feedback that while online PE-CPD provides new opportunities, there are still significant limitations. This research provides novel insights and valuable recommendations that could optimise the success of future online PE-CPD offerings.